The role of interfacial tension in the size-dependent phase separation of atmospheric aerosol particles - R. Schmedding; A. Zuend (Atmospheric Chemistry and Physics)
Atmospheric aerosol particles span orders of magnitude in size. In ultrafine particles, the energetic contributions of surfaces and interfaces to the Gibbs energy become significant and increase in importance as particle diameter decreases. For these particles, the thermodynamic equilibrium state depends on size, composition, and temperature. Various aerosol systems have been observed to undergo liquid–liquid phase separation (LLPS), impacting equilibrium gas–particle partitioning, modifying physicochemical properties of the particle phases, and influencing cloud droplet activation. Numerous laboratory experiments have characterized the onset relative humidity of LLPS in larger aerosol particles and macroscopic bulk systems. However, in sufficiently small particles, the interfacial tension between two liquid phases constitutes an energetic barrier that may prevent the formation of an additional liquid phase. Determining said small-size limit is a key question.